Improved methods for carbon accounting for bioenergy: descriptions and evaluations - Pena, N.; Bird, D.N.; Zanchi, G. (2011)
Under the United Nations Framework Convention on Climate Change, carbon dioxide emissions from bioenergy are counted as carbon stock losses in the land use sector rather than in the energy sector. This method omits many emissions since many nations that source biomass for bioenergy do not have greenhouse gas obligations. Accounting systems have been proposed to address this omission. This working paper describes and classifies these accounting systems into three basic types. Type 1 counts carbon dioxide emissions from bioenergy combustion unaccounted for in the energy sector. Type 2 counts bioenergy combustion emission accounted for in the energy sector. Type 3 counts all other emissions along the supply chain, which are the responsibility of end users. The accounting systems are evaluated against three criteria: comprehensiveness, simplicity and scale independence. They are also evaluated again three key stakeholder goals: stimulation of rural economies and food security, greenhouse gas emission reductions and preservation of forests. The paper describes four key conclusions. First, Type 2 approaches incorporate more emissions than Type 1 in the real-world situation. Second, a Type 2 system that includes carbon dioxide uptake by vegetation in the land use sector ranks highly if stimulation of rural economies and food security is a priority. However, it may not preserve forests or stimulate bioenergy development. Third, policies can make Type 1 approaches effective. However, this may be of limited value if many countries remain outside the accounting system. Fourth, a Type 3 approach supports greenhouse gas emission reductions and preservation of forests but is less simple, and stimulation of the rural economy depends on the structure of the cap-and-trade system.